If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 3m + -1 = 9m + 6 + -5m Reorder the terms: 3 + -1 + 3m = 9m + 6 + -5m Combine like terms: 3 + -1 = 2 2 + 3m = 9m + 6 + -5m Reorder the terms: 2 + 3m = 6 + 9m + -5m Combine like terms: 9m + -5m = 4m 2 + 3m = 6 + 4m Solving 2 + 3m = 6 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 2 + 3m + -4m = 6 + 4m + -4m Combine like terms: 3m + -4m = -1m 2 + -1m = 6 + 4m + -4m Combine like terms: 4m + -4m = 0 2 + -1m = 6 + 0 2 + -1m = 6 Add '-2' to each side of the equation. 2 + -2 + -1m = 6 + -2 Combine like terms: 2 + -2 = 0 0 + -1m = 6 + -2 -1m = 6 + -2 Combine like terms: 6 + -2 = 4 -1m = 4 Divide each side by '-1'. m = -4 Simplifying m = -4
| 3(5X+4)-10X+9=51 | | 17+3y=5 | | Y-25=180 | | -2(x-8)+9=25 | | Y-25+x+52+96=360 | | -5-3b=4(b+4) | | x+2x+4=10 | | X+52+96=180 | | 26-2a=-2(6a+3)+2 | | y=1.5x-0.4 | | 4(2x+1)-3x=34 | | 3s+8=-9s | | 5x^5=20x^3 | | 2x^2-15x+27=0 | | 4x+2*8=9*4x | | -2(7r+1)-6=-64 | | 2x^2-7x+9=x+1 | | -7.5x=15.0 | | -36=-v+8(v-8) | | 5y=10x-15 | | 162=6x+6(x+7) | | x^2-18x+70=0 | | 6x-7y=49 | | 16-6b=8-7b | | 2x+4x+3x+5=50 | | 0.3n=12 | | 2x-50+4x-63+3x+20=360 | | 0.3=12 | | -3x+2=-8 | | x-7.2=-3.1 | | 11x+18=10x+4 | | 11x-4y=-12 |